Supercontinent-superplume coupling, true polar wander and plume mobility: Plate dominance in whole-mantle tectonics - Li, Zheng-Xiang; Zhong, S. (Elsevier, 2009)
Seismic tomography has illustrated convincingly the whole-mantle nature of mantle convection, and the lower mantle origin of the African and Pacific superplumes. However, questions remain regarding how tectonic plates, mantle superplumes and the convective mantle interplay with each other. Is the formation of mantle superplumes related to plate dynamics? Are mantle plumes and superplumes fixed relative to the Earth's rotation axis? Answers to these questions are fundamental for our understanding of the inner workings of the Earth's dynamic system. In this paper we review recent progresses in relevant fields and suggest that the Earth's history may have been dominated by cycles of supercontinent assembly and breakup, accompanied by superplume events. It has been speculated that circum-supercontinent subduction leads to the formation of antipodal superplumes corresponding to the positions of the supercontinents. The superplumes could bring themselves and the coupled supercontinents to equatorial positions through true polar wander events, and eventually lead to the breakup of the supercontinents.